Motion Design Toolkit : Principles, Practice, and Techniques - Shaw, Austin, ....-; Colette, John, ....-; Shaw, Danielle, ....- (New York : Routledge, 2023)
This book offers a comprehensive overview of techniques, processes, and professional practices in the area of Motion Design, from fundamental building blocks of organizing time and space in production to managing workflow, budgets, and client relationships. The authors provide insight into the production process from concept through execution in areas as diverse as social media to large-scale projection mapping for events and festivals. Readers will learn through real-world examples, case studies, and interviews how to effectively use their skills in various areas of Motion Design. Industry professionals provide unique perspectives on different areas of Motion Design while showcasing their outstanding and inspiring work throughout. This is a valuable resource to students who aspire to work in a broad range of visual communication disciplines and expand their practice of Motion Design.
Keywords: Motion Design